Quality of life in cochlear implant users - Abreu, Jéssica Amanda (2020)
Purpose: To evaluate the quality of life of cochlear implant users. Methods: Cross-sectional, observational and descriptive study, in which the World Health Organization Quality of Life-bref (WHOQOL-bref) questionnaire was applied to assess quality of life. The questionnaire assesses the physical, psychological, social relations and environment domains. Speech recognition was also assessed using an open set sentence test. The study included 25 cochlear implant users with at least one year of use, older than 18 years old, with a mean age of 46.79 years. For data analysis, the following statistical tests were used: Spearman's correlation, ANOVA test and T-Student test (p-value <0.05). Results: Users of cochlear implants obtained an average of 78.70% correct answers in the speech recognition test of sentences in open set, in silence. It was observed in the WHOQOL-bref questionnaire that in the question of “global quality of life” and in the “psychological” domain, patients performed better, these scores being close to those of normal listeners. The “environment” domain was the one that patients had the worst performance. Conclusion: Patients demonstrated good quality of life, performing better in the “psychological” domain and presenting a satisfactory self-assessment of quality of life. It is suggested that the WHOQOL-bref questionnaire be used to complement the monitoring of cochlear implant users.